(B)
To solve this sort of system....
(a) place one equation in terms of one of the two variables. Let's place the first equation in terms of x (move everything to the other side):
x - y = -5
x = y - 5
(b) use that value to substitute into the other equation. In this case, we'll replace "x" with "y-5" in the second equation. Then solve the equation, which is now in terms of y only, for y:
2y = -2 - 2x
2y = -2 - 2(y-5)
2y = -2 -2y +10
4y = 8
y = 2
(c) Now that you have y, plug in that value in either original equation to calculate x:
x - y = -5
x - (2) = -5
x = -3
That's the solution. x=-3, y=2, or (-3,2), which is your answer (B).
(d) To check your solution, plug those values into the OTHER equation, whichever one you didn't use in step (c) above:
2y =? -2 - 2x
2*2 =? -2 -2*(-3)
4 =? -2 - (-6)
4 = 4
This is always a good idea, because it helps catch simple mistakes.
2007-07-03 09:33:28
·
answer #1
·
answered by McFate 7
·
0⤊
1⤋
First, solve the first equation for x, by adding y to both sides of the equation:
x - y + y = -5 + y
x = y - 5
Next, substitute x of equation 1 (y -5) into the second equation:
2y = -2 -2(y-5)
Distribute -2 into the parenthetical expression:
2y = -2 -2y + 10
Get all the y's on one side of the equation by adding 2y to each side of the equation:
2y + 2y = -2 -2y +10 + 2y
4y = 8
Divide both sides by 4 to get y alone:
y = 2
Now substitute the value for y (in this case, 2) into equation 1 to find x:
x - 2 = -5
Add 2 to both sides of the equation to get x alone:
x - 2 + 2 = -5 + 2
x = -3
So we have x = -3, y = 2, or (-3,2), B.
This is called the substitution method of solving a couple equations.
2007-07-03 16:41:54
·
answer #2
·
answered by sratree42 2
·
0⤊
0⤋
2x + 2y = -2 Thus x + y = -1
Add this to x - y = -5
So, you get 2x = -6
x = -3
Plugging back into x -y = -5 gives -3 - y = -5 or
y = 2.
If all else fails, just plug in all the options and see if which one works.
The answer is B (-3, 2)
2007-07-03 16:36:32
·
answer #3
·
answered by MathProf 4
·
0⤊
0⤋
2(x - y = -5)
2x+2y=-2
2x-2y=-10
2x+2y=-2
4x= -12
x= -3
-3-y=-5
-y=-2
y=2
answer is B
2007-07-03 16:38:58
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
Plug in the (x,y) and you will see that B works for the two equations.
2007-07-03 16:35:09
·
answer #5
·
answered by millie 2
·
0⤊
0⤋
first either the absolute value of x+y or (x-y or y-x) must equal five so you are down to A, B, and F
Then just plug and chug The answer is...
B
2007-07-03 16:35:27
·
answer #6
·
answered by giantsfan2002_69 2
·
0⤊
0⤋